Multistructured Accretion Flow of Sgr A*. II. Signatures of a Cool Accretion Disk in Hydrodynamic Simulations of Stellar Winds - Mayura Balakrishnan; Christopher M. P. Russell; Lia Corrales; Diego Calderón; Jorge Cuadra; Daryl Haggard; Sera Markoff; Joey Neilsen; Michael Nowak; Q. Daniel Wang; Frederick Baganoff (The Astrophysical Journal, 2024)
Hydrodynamic simulations of the stellar winds from Wolf–Rayet stars within the Galactic center can provide predictions for the X-ray spectrum of the supermassive black hole Sgr A*. Herein, we present results from updated smooth particle hydrodynamics simulations, building on the architecture of Cuadra et al. and Russell et al., and find that a “cold” (10 ^4 K) gas disk forms around Sgr A* with a simulation runtime of 3500 yr. This result is consistent with previous grid-based simulations, demonstrating that a cold disk can form regardless of numerical method. We examine the plasma scenarios arising from an environment with and without this cold disk, by generating synthetic spectra for comparison to the quiescent Fe K α Sgr A* spectrum from Chandra HETGS, taken through the Chandra X-ray Visionary Program. We find that current and future X-ray missions are unlikely to distinguish between the kinematic signatures in the plasma in these two scenarios. Nonetheless, the stellar wind plasma model presents a good fit to the dispersed Chandra spectra within 1.″5 of Sgr A*. We compare our results to the radiatively inefficient accretion flow (RIAF) model fit to the HETGS spectrum presented in Paper I and find that the Bayesian model evidence does not strongly favor either model. With 9″ angular resolution and high spectral resolution of the X-IFU, NewAthena will offer a clearer differentiation between the RIAF plasma model and hydrodynamic simulations, but only a future X-ray mission with arcsecond resolution will significantly advance our understanding of Sgr A*’s accretion flow in X-rays.